O Centro de Divulgação Científica Cultural da Univerisdade de São Paulo, campus São Carlos: um projeto de extensão universitária - Canales, Renata Pereira (Universidade Federal de São Carlos, 2006)
The present study endeavours to contribute to a better understanding of the education in this country by means of a case study of the Centro de Divulgação Científica e Cultural CDCC (Centre for Scientific and Cultural Promotion). This centre was established in 1980 by the São Carlos campus of the University of São Paulo and since then put under the care of the Institute of Physics and Chemistry. The CDCC operates educational projects aimed at fostering scientific curiosity in basic educational level students. The investigation covers the process of CDCC s creation and seeks comprehension of its first motivation and objectives as well as peruses into the history of its building, which once hosted the Engineering School of USP-São Carlos. It does also investigate the services offered to the community, analyses CDCC administrative rules, and more incisively, reasons out the role of the Experimentoteca , the initial project that begot the Centre itself, and whose scope is to provide means of empirical experience of scientific theories for children at the basic level of education. The Experimentoteca is a portable laboratory of sciences that, under request, is taken to schools for classroom demonstrations. This project, initially restricted to São Carlos City and region, is currently extended to 31 cities of 13 different states. Following the steps of Buffa and Nosella, an epistemological frame of reference is taken from work and educational relations as well as from the relations of general overview and singular descriptions, as established by the New History, along with analysis of documents and facts under the educational viewpoint of the country. The sources are both the literature concerning community roles of the university, defined as one of the corners of the university s triple mainstay in the 5,540/68 Bill and the 1988 Constitution, and yet the literature concerning the history of Brazilian education, chiefly after the 5,692/71 Bill, which was in force when the CDCC was created. Additional research sources are magazines, books, scientific articles concerning the CDCC and its building, as well as CDCC s reports and governance rules. Interviews with CDCC s workers and founders and questionnaires applied to students using the Experimentoteca are yet complementary sources. Data analyses avail a conclusion that CDCC orientation differs from the patronizing stance that pervades most of community services. Indeed, evidence was produced as to suggest that CDCC s intervention fosters reflection and responsibility among students. Nevertheless, the scientific curiosity does not seem to blossom as expected. School and social-family adverse environments do not make room for such: these are children of low income working class parents, who are educationally deprived and subjected by a neglected educational policy that includes deteriorated buildings, unhealthy classrooms, and teachers discouraged by low wages and bad working conditions. The CDCC s work stands alike a clean drop over a polluted river but its initiative is not useless, and does meet its best meaning in the respect to citizenship and in the interchange of lay and academic wisdom provided by the collaboration between university and community. There remains a hope that such values that exceed school limits be dully appreciated by the country politicians.
Keywords: Extensão universitária; Experimentoteca; CDCC; CDCC; Community roles of the university; Experimentoteca; CIENCIAS HUMANAS::EDUCACAO